The impact of job empowerment on the performance of female employees at Umm Al-Qura University in Mecca, 2021 - Al-Ghamdi, Ashwaq Saeed (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aims to identify the reality and level of job empowerment at UQU, and the level of female employees ’performance, to identify the most important obstacles to job empowerment and to reveal the extent of the impact of job empowerment on the performance of female employees at UQU, and to identify statistically significant differences about the impact of job empowerment.  The performance of female employees is attributed to the type of job (academic, administrative).  To achieve these objectives , the researcher used the descriptive methods , the questionnaire information-gathering tool was built in five main axes related to the objectives of the research. The questionnaire tool was applied to a sample consisting of (57) samples from the administrators and employees of UQU . After analyzing the data and treating it statistically, there was many results from the study , the most important were the presence of a high level of job empowerment, a high level of job performance, a medium level of job empowerment obstacles, and a high impact of job empowerment on the performance of female employees at UQU. In light of the results of the study, the researcher recommended that the university be keen to continue to use work teams in accomplishing work and solving problems and doing, which has a positive role in consolidating collective responsibility and therefore responsibility for decisions and solutions and commitment to implement them and give employees motivation to work better By involving it and thus improving the job performance, and UQU adopt career empowerment as an administrative method, in order to raise awareness of this aspect, given its importance in improving and developing the performance of female employees, which leads to the achievement of the university's objectives.
Keywords: job empowerment; Performance of female employees; Umm Al Qura University; Mecca city